The functional significance of complex floral colour pattern in a food-deceptive orchid - Ma X. (2017)
© 2016 British Ecological Society. Many non-rewarding orchid species mimic the signals of co-occurring food flowers and thereby attract food-seeking animal pollinators. These signals are often visually complex with a colour pattern that contrasts between outer and central parts. The significance of this colour complexity for the pollination success of flowers of deceptive orchids has scarcely been investigated. We tested the effects of the colour patterns of the food-deceptive orchid Paphiopedilum micranthum on bumblebee visitation choices and pollination success using behavioural experiments in a community context. Using comparative phylogenetic analysis and a bee vision model, we also compared the colour patterns of P. micranthum with those of its congeners and sympatric food flowers. The probability of both long-range approach and close-up choice by bumblebees to orchids was all enhanced in communities with food flowers similar in colour pattern to the orchid. Probability of long-range approach and close-up choice was negatively correlated with colour distance between orchid and food flowers in floral outer and centre, respectively. Flowers of P. micranthum that were manipulated to reduce visual complexity had reduced male and female pollination success. Phylogenetic analysis revealed that the outer floral colour of P. micranthum is apomorphic and thus likely represents an evolutionary innovation, whereas the central colour is plesiomorphic and thus likely to function in the bumblebee pollination system as an exaptation. The contrast between the inner and outer colours appears to exploit visual preferences of bumblebees acquired during foraging on local food plants with similar colour patterns. This study highlights the adaptive significance of colour patterns in successful food deception and the importance of complex signals in facilitating interspecific interactions.